Emotional Intelligence of Medical and Dental Doctors with Different Clinical Experiences: A Cross Sectional Study - Marium Sohail , Raheela Yasmin , Amina Ahmad , Rafia Illyas (Journal of Islamic International Medical College, 2021)
Objectives: To measure Emotional intelligence scores of medical and dental doctors with different years of clinical experience.To establish a correlation between domain specific Emotional Intelligence scores and years of clinical experience of medical and dental doctors. Study Design: A Quantitative; Cross-sectional Survey was conducted at Fatima memorial college of Medicine & Dentistry, Lahore. Place and Duration of Study: Study was conducted from August 4 , 2019 to October 6 , 2019 i.e. (2 months) duration. Materials and Methods: A total of 150 medical and dental doctors were selected using convenience sampling in 3 different categories according to clinical experience. After ethical approval & informed consent of participants, data was collected using pre-validated “Leadership Toolkit Emotional Intelligence Questionnaire.” Data was summarized using descriptive statistics in SPSS 23. Mean and standard deviation for each group was calculated. Comparison between groups & five domains of EI was using cross tabulation & Pearson's chi-square test. Results: A total of 150 doctors with 55.3% females and 44.7% males participated in the study. Emotional quotient was assessed based on 5 domains by plotting responses on 5-point Likert scale. Majority of the participants scored, well in self-awareness (63%), empathy (66%), while low in managing emotions (37.3%), self-motivation (45%) and social skills (38%). Total global-EI score increases with years of experience. Consultants scored statistically higher in all domains except managing emotions. House-officers scored lowest in managing emotions while post-graduates scored lowest in social skills. Conclusion: There is a positive correlation between global EI scores and years of clinical experience with a downward trend in scores of self-motivation and social skills among post graduate trainees.